Poverty and Inequality: Contemporary Issues in Nigerian Fourth Republic - Alaye, Adekunle (Acta Universitatis Danubius. Juridica, 2024)
Nigeria, Africa’s most populous nation and a major oil producer is confronted with several challenges, including scarcity of valuable resources. Despite the abundance of natural resources and a potentially growing economy, the country struggles with entrenched poverty and stark socioeconomic inequalities. Previous studies have focused on poverty and socioeconomic challenges, little have been done on the reflection in the fourth republic. This study examined poverty and inequality in the fourth republic, with a view to underscoring the impact on socioeconomic development, determining the extent of evolvement over the years and investigate the factors contributing to poverty and inequality. Qualitative design was used. Data was collected using interviews with individuals and communities impacted by poverty and inequality. 20 respondents were purposively selected. Enzo Feletto’s Dependency and Karl Max’s Structural theory served as the theoretical framework. Income inequality, gender discrimination, and unequal access to political and legal system manifested as critical factors perpetuating poverty and restricting opportunities for marginalized groups. The causes of poverty and inequality were inadequate infrastructure, poor governance and corruption, which limited economic participation and productivity. Policies aimed at economic diversification, improving access to education and strengthening social safety nets should be used to combat poverty and inequality, to enhance socioeconomic development of Nigeria.